2011
DOI: 10.1002/ijc.25476
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for the development of chronic atrophic gastritis: Five year follow‐up of a population‐based cohort study

Abstract: Chronic atrophic gastritis (CAG) is a well-established precursor of intestinal gastric cancer. However, data on incidence of CAG are rare, especially from population-based studies. The aim of this analysis was to estimate the incidence of CAG in a large population-based study among older adults from Germany and to identify major risk factors associated with its development. In the baseline and 5-year follow-up examinations of the ESTHER study, serological measurements of pepsinogen (PG) I and II and Helicobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 61 publications
2
42
1
2
Order By: Relevance
“…Although cytotoxin associated gene A (cagA) has also been anticipated as a new biomarker for gastric cancer, its use has been limited to research-based screening [33] . Most of the reported studies are cross-sectional studies in which the serologic test was performed simultaneously with upper endoscopic screening.…”
Section: Endoscopic Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cytotoxin associated gene A (cagA) has also been anticipated as a new biomarker for gastric cancer, its use has been limited to research-based screening [33] . Most of the reported studies are cross-sectional studies in which the serologic test was performed simultaneously with upper endoscopic screening.…”
Section: Endoscopic Screeningmentioning
confidence: 99%
“…Most of the reported studies are cross-sectional studies in which the serologic test was performed simultaneously with upper endoscopic screening. Although several studies have been reported from European countries, their outcomes were mainly for chronic atrophic gastritis which is a surrogate endpoint even if it can be a precursor of gastric cancer [33][34][35] . Lomba-Viana et al [36] previously reported the results of a 5-year follow-up study of the serum pepsinogen test for the early detection of gastric cancer in Portugal.…”
Section: Endoscopic Screeningmentioning
confidence: 99%
“…The association of HP infection with GC and GA has been known, previously (Adamu et al, 2011;Correa, 1992 prevalence of HP infection in our area. Therefore, it is recommended to consider HP infection for conducting GC controlling programs (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…It has been reported that infection with H. pylori is a risk factor for gastric cancer (The Eurogast Study Group 1993;McFarlane and Munro 1997). H. pylori infection is the key determinant in fundic atrophy development (Adamu et al 2011), which also affects pepsinogen and gastrin secretion (Gatta et al 2011). H. pylori infection results in chronic gastritis that will develop into atrophic gastritis of some grade or type in half of infected subjects during their lifetime (Valle et al 1996;Maaroos et al 1999).…”
Section: Discussionmentioning
confidence: 99%